(untitled) (Swiss Medical Weekly, 2010)
Osteoarthritis (OA), also known as degenerative joint disease, is the most frequent chronic musculoskeletal disease and the leading cause of disability in elderly persons. There are currently at least 27 million persons afflicted with OA in the United States, and the annual cost to society in medical care and wage loss is expected to reach nearly 100 billion dollars by 2020, with consequent increased spending on its diagnosis and treatment, side effect prevention, and loss of productivity. Despite this enormous burden, many aspects of OA are still unknown, with implications not only in terms of diagnosis and assessment but also with regard to therapy. Awareness of this state of affairs has attracted many researchers to this field, making OA one of the most actively studied sectors of rheumatology. Although some clinicians are unaware of recent advances, there is a large body of publications indicating that much has been achieved. Major progress has been made in formulating better definitions of risk factors, in particular in indicating the responsibility of biomechanical and genetic factors, and, with regard to pathogenesis, underlining the role of subchondral bone, cytokines and proteinases. Assessment of OA activity and its progression has been improved with the advent of biomarkers and new imaging procedures, in particular sonography and magnetic resonance imaging (MRI), but also of better clinical instruments, including more reliable patient questionnaires. Information from ongoing studies may improve the to some extent incomplete definition of OA phenotypes. Finally, promising new horizons have been opened up even with regard to the treatment of OA, which is still for the most part unsatisfactory except for surgical replacement therapy. Numerous new substances have been formulated and the findings of trials studying their effects are encouraging, although much has yet to be done.